Cathelicidin as a link between sarcoidosis and tuberculosis - Korucu, Ercan; Pur Ozyigit, Leyla; Ortakoylu, Mediha Gonenc; Bahadir, Ayse; Akalin, Esma Seda; Kara, Asuman; Uzun, Hafize; Onal, Burak; Caglar, Emel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
ABSTRACTSetting: Sarcoidosis and tuberculosis share notable clinical, radiological, histological, and immunological similarities. The importance of vitamin D has long been investigated in these two granulomatous lung diseases. Cathelicidin is an antimicrobial peptide of the innate immune system, directly induced by vitD3.Objective: To evaluate the role of cathelicidin in sarcoidosis and tuberculosis development.Design: The study included 30 consecutive patients with active lung tuberculosis, 30 patients with sarcoidosis, and 20 healthy controls. 25-hydroxyvitamin D [25(OH)D] and cathelicidin levels were measured in blood samples.Results: Vitamin D levels were significantly higher (p